how would you do this prob.
negative4-(5y+6) = negative 7y+3
thanks.
happy halloween
I'm going to assume your problem is this:
-4 - (5y + 6) = -7y + 3
If that's the case, distribute the negative over the terms in the parentheses first:
-4 - 5y - 6 = -7y + 3
Combine like terms:
-5y - 10 = -7y + 3
Let's add 7y to both sides of the equation (whatever operation you do to one side of an equation you must do to the other side as well):
-5y + 7y - 10 = -7y + 7y + 3
2y - 10 = 3 -->we now have the variable on one side of the equation.
Let's add 10 to both sides:
2y - 10 + 10 = 3 + 10
2y = 13
Now divide both sides by 2 to get y by itself and solve the equation:
2y/2 = 13/2
y = 13/2
Substitute this value for y into the original equation to check. It always helps to check your work!
I hope this was your problem.